EPISTEMOLOGI KONSUMSI HALAL DALAM PERSPEKTIF ISLAM - Mufti Fahrizal Harahap (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
The main economic activity is consumption. After consumption and new consumers there are other activities such as production/producer, distribution/distributor and others. Consumption in Islam is an effort to meet both physical and spiritual needs so that they are able to maximize their human function as a servant of Allah to obtain prosperity or happiness in the world and the hereafter (falah). This research is a type of descriptive paper (descriptive research) with qualitative research, namely research procedures that produce descriptive data in the form of written words from people and observed behavior, supported by literature studies or literature studies based on an in-depth literature review, so that reality well understood. In doing consumption, consumer behavior, especially Muslims, is always and must be based on Islamic Sharia. The influence of food on human life is very large and it also affects one's soul, including prayer, making the soul calm, then a bribe that is forbidden into the stomach, it will not be accepted by its deeds for forty days, bad food will damage health and destructive also to the mind.